Effects of religious celebrity on destination experience: The case of Pope Francis's visit to Solmoe Shrine. (31st July 2019) - Kim, Bona; Chen, Yong
Abstract: A wealth of academic research has been devoted to examining the effects of secular celebrities rather than religious celebrities on individuals' destination experiences at the pilgrimage destination. We aim to investigate the effects of a religious celebrity on how visitors perceive a destination as well as their pilgrimage experience. Our study has shown that the indirect effects of religious celebrity on destination‐related constructs in the context of a pilgrimage site are robust. These results suggest that spirituality is a crucial mediator in shaping travel experience, through which visitors can close the gap between pilgrimage on the spiritual side and their consumption experience on the pilgrimage destination side.